Man Jadda Wajada: Religious Aspects in Negeri 5 Menara by Ahmad Fuadi: A Semiotic Analysis - Margawati, Prayudias (Universitas Negeri Semarang, 2022)
This study aimed at describing the religious aspects in Negeri 5 Menara, a novel by Ahmad Fuadi. To analyze the novel, the structural method was implemented to operationally describe the intrinsic elements of the novel. To reveal the meanings of the novel as a semiotic phenomenon, heuristic and hermeneutic methods were also implemented. The religious aspect found in the novel was a shared mission that brought the characters to Pondok Pesantren Madani (pondok pesantren means Islamic boarding house, which is also briefly referred to as pondok or pesantren) as santris (santri means a student of Islamic boarding house) and united them in an environment full of religious values. A proverb from hadith saying Man Jadda Wajada (whoever strives shall succeed) was clearly manifested by all characters, including the teachers and the santris. The moral messages depicted by the author through the narratives of intellectuality and spirituality clearly indicated religious values of this novel.